Faldaprevir (Bi 201335), Deleobuvir (Bi 207127) and Ribavirin Oral Therapy for Treatment-Naive HCV Genotype 1: Sound-C1 Final Results. Issue 8 (November 2013) - Zeuzem, Stefan; Asselah, Tarik; Angus, Peter; Zarski, Jean-Pierre; Larrey, Dominique; Müllhaupt, Beat; Gane, Ed; Schuchmann, Marcus; Lohse, Ansgar W; Pol, Stanislas; Bronowicki, Jean-Pierre; Roberts, Stuart; et al.
Background: Faldaprevir (BI 201335) and deleobuvir (BI 207127) are direct-acting antiviral agents under development for the treatment of chronic HCV infection. This article describes the final results of the Phase Ib SOUND-C1 study that evaluated the interferon-free oral combination of faldaprevir, deleobuvir and ribavirin in 32 treatment-naive patients infected with HCV genotype 1. Methods: Patients were randomized to receive deleobuvir 400 mg ( n =15) or 600 mg ( n =17) three times daily plus faldaprevir 120 mg once daily and weight-based ribavirin for 4 weeks. Interferon-free therapy was followed by response-guided faldaprevir plus pegylated interferon-α2a/ribavirin to week 24 or 48. Results: At week 4, 73% (11/15) and 100% (17/17) of patients in the deleobuvir 400 mg and 600 mg groups achieved HCV RNA<25 IU/ml, respectively. During interferon-free treatment, virological breakthrough was reported in one patient and re-increase of HCV RNA in one patient. Both patients were successfully treated with interferon-containing therapy. The rate of sustained virological response 24 weeks after completion of treatment was 73% (11/15) in the deleobuvir 400 mg group and 94% (16/17) in the 600 mg group. During faldaprevir plus pegylated interferon-α2a/ ribavirin treatment, the most common adverse events were pruritus (38% of patients), rash (31%) and asthenia (31%); these were severe in approximately 3% of patients. Conclusions: Potent antiviral activity and favourable safety of the treatment regimen were demonstrated. Furthermore, the results suggest that patients with breakthrough at week 4 may be rescued with an interferon-containing regimen. Clinical trials.gov number NCT01132313.